Analisis in Silico Senyawa Fitokimia dari Fraksi n-Heksana Daun Semanggi (Marsilea crenata Presl.) sebagai Agen Neuroprotektif - Ma'arif, Burhan; Jatmiko, Ricky Arie; Megawati, Dewi Sinta; Annisa, Rahmi; Sugihantoro, Hajar; Muchlisin, Muhammad Artabah; Laswati, Hening; Agil, Mangestuti (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Estrogen deficiency causes various health problems in postmenopausal women, including neurodegenerative disease. Phytoestrogens emerged as a group of compounds that can replace the estrogen function in the body, and prevent the neurodegenerative disease to occur. Semanggi (Marsilea crenata Presl.) is a typical plant in Surabaya, Indonesia, that contain phytoestrogens. The aim of this research was to determine the metabolite profile of n-hexane fraction of Semanggi leaves using UPLC-QToF-MS/MS, and then to predict the neuroprotective activity of compounds with in silico study using PyRX 0.8 software. The 100 ppm of n-hexane fraction of Semanggi leaves in DCM and methanol were injected 5 Âµl each into the UPLC-QToF-MS/MS, and then analyzed by Masslynx 4.1 software to determine the compounds. The compounds from metabolite profiling then prepared with SwissADME webtool and Avogadro 1.90.0 software, molecular docking was done using Autodock Vina and Biovia Discovery Studio Visualizer 2016 to 3OLS protein. Metabolite profiling process shows a total of 34 predictable compounds and 28 unknown compounds. From in silico study, it shows a total of 7 compounds that are predicted to have activities similar to estrogen. This result indicate that n-hexane fraction of Semanggi leaves has potential as a neuroprotective agent for treatment for postmenopausal women who experience estrogen deficiency.Keywords: Marsilea crenata Presl., phytoestrogens, metabolite profiling, in silico, neuroprotective